Mathematical creative thinking skills of eight grade in terms of learning styles on learning model Means-Ends Analysis (MEA) - Octaviana, Dina; Kurniasih, Ary Woro (Department of Mathematics, Universitas Negeri Semarang, 2020)
This study aims to test whether learning with the Means-Ends Analysis (MEA) model achieves learning completeness and knows the description of the ability to think creative with the MEA model in terms of student leraning styles. Research is a research mixed methods model of concurrent triangulation. The population of this research is students of class VIII one of Junior High School in Pekalongan in the academic year 2018/2019, a sample of students of class VIII-F. Research subjects were students of class VIII-F selected with purposive sampling technique, selected 4 students from the type of visual and auditory learning styles, and 3 students from the type of kinesthetic learning style. Quantitative data were analyzed using the one-party average test and the one-party proportion test. Whereas qualitative data were analyzed using the Miles adnd Huberman model, namely making verbal data transcripts, data reduction, data analysis, and making conclusions. The result showed that: (1) learning with the MEA model achieved mastery learning; and (2) description of creative thinking abilities of students with models of MEA in terms of students learning styles that students with visual learning style meet three indicators of creative thinking that fluency fluency, originality, and elaboration; students with learning styles of auditory almost all meet the four indicators of creative thinking that fluency, flexibility, originality, and elaboration; students with kinesthetic learning style meets the four indicators of creative thinking that fluency, flexibility, originality, and elaboration.